Bases para uma Educação Menstrual Popular e LGBTQIAPN+ - Chacon, Za Saggioro (2024)
This research arises in response to the lack of pedagogical references about a menstrual approach that includes the diversity of bodies that bleed, beyond the existing social boundaries of the term “people that menstruate”. It can be described also as a manifest from a nonbinary author searching for non cis-heterocentric answers for his menstrual experience. There is a scientific theoretical apparatus that describes the body that bleeds, anchored on discourses by the church, medicine, psychiatry and psychoanalysis, together with conceptions of gender that are based on the dictatorship of sexual difference. Both cis women, the universal subject, and trans people, have a history of definitions, narrated by these same institutions, from a pathological bias. The difference is that only the first is related, in an essentialistic and stigmatized way, to the experience of bleeding. The goal, given this scenario, is to propose menstrual practices and the search of educational processes that could contribute to a more popular and inclusive menstrual approach from the perspective of the diversity of bodies that bleed. As it is a study intrinsically linked to the principles of Educação Popular em Saúde (EPS), data collection was adapted to the conext demands and included a moment of participatory investigation and an autoethnographic narrative about my gender transition to better represent the exchanges that constructed the research. As a result of this process, foundations were determined for any space that wishes to discuss menstruation in a popular and LGBTQIAPN+ centric approach, paving the way for the construction of practices committed to a trans-referenced and post-heterocolonialist epistemology, as well as the design of a game that encourages menstrual debates.